The influence of knee osteoarthritis on the balance and gait of elderly individuals (Research, Society and Development, 2021)
Aim: To affect the influence that osteoarthrosis has on the balance and gait of elderly patients. Method: This is an observational study in elderly people of both genders with diagnosed knee osteoarthritis. Initially, a lecture was held on the objectives of the study and after signing the Informed Consent Term, the collection of sociodemographic data was carried out; pain assessment using the visual analogue scale; balance assessment using the Berg Balance Scale, mobility and gait assessment using the Time Up and Go and Tinetti Test. Results: Eleven elderly people with osteoarthritis, all female, with a mean age of 75.6 years, were selected for the study. There was a correlation between increasing age and worsening mobility and balance in the elderly. Conclusion: It was concluded in this research, that aging is a physiological and progressive process, in which several body systems are compromised, mainly the musculoskeletal system. Aspects such as balance and morbidity have a strong relationship with advancing age and may have physical and psychological impairment.